2013
DOI: 10.3390/polym5010128
|View full text |Cite
|
Sign up to set email alerts
|

Biodegradable Poly(butylene succinate) Composites Reinforced by Cotton Fiber with Silane Coupling Agent

Abstract: In this study, the use of cotton fiber (CF) as a filler in poly(butylene succinate) (PBS) and the effect of silane treatment on the mechanical properties, thermal stability, and biodegradability of PBS/CF composites are investigated. The results showed that the tensile strength of PBS was improved (15%–78%) with the incorporation of CF (10–40 wt%) and was further increased (25%–118%) when CF was treated with a silane coupling agent. Scanning electron microscopy (SEM) observation of the fracture surfaces of PBS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
51
0
1

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 110 publications
(67 citation statements)
references
References 34 publications
2
51
0
1
Order By: Relevance
“…Glass transition temperature ( T g ), crystallization temperature ( T c ), cold crystallization ( T cc ), melting temperature ( T m ), and specific fusion enthalpy ( ∆H f ) were evaluated from the endothermic and exothermic peaks. The degree of crystallinity ( χ c ) of the blend film was calculated from the following Equation 2: χc()%=ΔHnormalf,blend()0.7ΔH0f,PLA+0.3ΔH0f,PBS×100 where ΔH f, blend is the specific fusion enthalpy of the blend films, ΔH 0 f, PLA is specific fusion enthalpy of 100% crystalline PLA (93.6 J/g), and ΔH 0 f, PBS is the specific fusion enthalpy of 100 crystalline PBS (110.3 J/g) …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Glass transition temperature ( T g ), crystallization temperature ( T c ), cold crystallization ( T cc ), melting temperature ( T m ), and specific fusion enthalpy ( ∆H f ) were evaluated from the endothermic and exothermic peaks. The degree of crystallinity ( χ c ) of the blend film was calculated from the following Equation 2: χc()%=ΔHnormalf,blend()0.7ΔH0f,PLA+0.3ΔH0f,PBS×100 where ΔH f, blend is the specific fusion enthalpy of the blend films, ΔH 0 f, PLA is specific fusion enthalpy of 100% crystalline PLA (93.6 J/g), and ΔH 0 f, PBS is the specific fusion enthalpy of 100 crystalline PBS (110.3 J/g) …”
Section: Methodsmentioning
confidence: 99%
“…where ΔH f, blend is the specific fusion enthalpy of the blend films, ΔH 0 f, PLA is specific fusion enthalpy of 100% crystalline PLA (93.6 J/g), 26 and ΔH 0 f, PBS is the specific fusion enthalpy of 100 crystalline PBS (110.3 J/g). 27…”
Section: Differential Scanning Calorimeter Measurementmentioning
confidence: 99%
“…Marco Valente introduced recycled paper in high density polyethylene matrix composites which additivated with maleated PE. Also, silane coupling agents, such as 3‐aminopropyltriethoxysilane, 3‐aminopropyltrimethoxysilane, and N1‐3‐trimethoxysilylpropyldiethylene triamine have used as compatibilizers by Calabia . Although these studies showed that the mechanical properties and some other properties of materials were improved to a certain extent, they generally had some defects during the modification process, such as low reaction rate of the compatibilizers, low proportion of plant fiber, not to mention the establishment of the effective interface structure.…”
Section: Introductionmentioning
confidence: 99%
“…Also, silane coupling agents, such as 3-aminopropyltriethoxysilane, 3-aminopropyltrimethoxysilane, and N1-3-trimethoxysilylpropyldiethylene triamine have used as compatibilizers by Calabia. [23] Although these studies showed that the mechanical properties and some other properties of materials were improved to a certain extent, they generally had some defects during the modification process, such as low reaction rate of the compatibilizers, low proportion of plant fiber, not to mention the establishment of the effective interface structure. Furthermore, the extensive use of organic solvents such as dimethyl sulfoxide, tetrahydrofuran and toluene inevitably produced severe environmental pollution during their processing.…”
Section: Introductionmentioning
confidence: 99%
“…Development and characterization of composites produced from cotton fibers reinforced with various matrices have been explored by a few researchers. Cotton-epoxy [6], cotton-polyethylene [7], cotton-butylene succinate [8], cotton-phenolic [9], textile cotton-polypropylene [10], cotton-geopolymer [11], cotton-bionolle 3020 [12], cotton-vinyl ester [13], jute/cottonphenolic [14], cotton-polyester [15] are some of the promising systems.…”
Section: Introductionmentioning
confidence: 99%